REVIEW ARTIKEL : UJI EFEK ANTI AGING DARI BERBAGAI EKSTRAK TUMBUHAN SECARA IN VIVO DAN IN VITRO - Febriyanti, Triana; Sukohar, Asep; Pardilawati, Citra Yuliyanda; Adjeng, Andi Nafisah Tendri (Medula, 2024)
The outermost and largest organ in our body is the skin. Skin can experience aging when exposed to sunlight. Sunlight contains ultraviolet. Exposure to ultraviolet (UV) radiation causes damage to the skin and can lead to photoaging. Photoaging can be prevented with antioxidant compounds. Many plant extracts or synthetic compounds act as anti-aging agents. These plant extracts become active ingredients that can be formulated into pharmaceutical preparations. Plant extracts that have anti-aging potential include red cabbage, kepok banana peel, red pomegranate, moringa leaves, butterfly pea flower, black cumin seeds and libo fruit. To prove this, a test was carried out. The testing carried out can be in the form of in vivo and in vitro testing methods. This research was carried out using the article review method and obtained several journals from online literature, local journals and international journals, namely electronic searches with the keywords anti-aging, in vitro, in vivo on the website, namely Google Scholar. The number of journals used in this review was 11 journals spanning the last eight years. The results of the article review study showed that several methods used were UV-VIS spectrophotometer, DPPH method, anti-elastase, as well as tests on rats, mice and guinea pigs. From the results of the review of articles on plant extracts, most of them use in vivo tests on experimental animals.